42.4L: Late‐News Paper: Footprint of Scalable 3D Telecommunication: Using Integral Light Field Display and Kinect‐based Capture. Issue 1 (1st July 2013) - Peng, Yifan; Zhong, Qing; Han, Xiang; Yuan, Li; Wang, Rui; Bao, Hujun; Li, Haifeng; Liu, Xu
Abstract A footprint of 3D telecommunication system is introduced, using integral light field display and Kinect‐based capture. Two prototypes with LCD‐based projection display and multi‐projectors‐based display, respectively, are developed to perform the 3D display. Kinect‐based 3D capture is integrated in providing preliminary and real‐time human model capture. This approach is scalable and demonstrated as a potential solution for market‐oriented 3D telecommunication.